Develop and evaluate effect of patient satisfaction training module for nurses based on patient satisfaction index regarding nursing services in a teaching hospital, Navi Mumbai - Kumar Prajapat, Vinod; Veer, Bharati (International Journal of Nursing Research, 2023)
Aim: The aim of study, To assess Patient Satisfaction Index after implementation of patient satisfaction training module, To determine the factors influencing patient satisfaction as perceived by the nurses. Materials and method: A research approach adopted for this study was descriptive evaluative approach with two-group pre-test, post-test design. The study was based on Imogene goal attainment theory. Patients on the day of discharge and nurses working in medical-surgical words were selected by nonprobability convenience sampling. A study conducted on 30 nurses and two groups of the patients. Group- A for pre-test and group- B for post-test each with 100 sample sizes. Data regarding patient’s satisfaction and factors influencing patient’s satisfaction was collected through self-reported five points Likert scale. Results: The findings review that patient satisfaction training module was effective in improving patient’s satisfaction. There is significant difference was noted in the agreement percentage related to all fractures influencing patient satisfaction as perceived by nurses before and after implementation of patient satisfaction training module. Conclusion: Thus, it is concluded that the patient’s satisfaction training module is effectively improving the patient’s satisfaction index and nursing services. A significant change was observed in patient satisfaction index and factors affecting patient satisfaction as perceived by nurses.